Comparative analysis of phytonutrients of Moringa oleifera leaves from South Africa and Nigeria, and their antimicrobial and antioxidant potentials by UPLC-ESI-QToF-MS and OPLS-DA chemometric analysis - Kayembe, Jonathan; Sekelwa, Cosa; Bassey, Kokoette (Frontiers in Nutrition, 2025)
BackgroundMoringa oleifera Lam. has bioactive phytonutrients in abundance and offers diverse health benefits. The leaves of this plant have established significance in traditional medicine and nutrition. It is traditionally used by Nigerian and South African mothers to mitigate undernutrition. Usually, the powder leaves are added to porridge to feed the children. This study aimed to conduct a comparative analysis of the phytonutrients (nutrients protectors) or supplements, antioxidant, and antimicrobial potentials of M. oleifera leaves from Nigeria and South Africa to benchmark quality control protocols for commercial beverages such as Moringa porridge.MethodsStandard techniques, including high-performance liquid chromatography-photodiode array and ultra-high-performance liquid chromatography electrospray ionization quadruple time-of-flight mass spectrometry (UPLC-ESI-QToF-MS) and chemometrics orthogonal partial least square discriminant analysis (OPLS-DA) were employed for phytoconstituents fingerprinting. Whereas the antioxidant potentials of the extracts were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide scavenging assays, the antimicrobial potentials of the extracts were evaluated using minimum inhibitory concentrations protocol.ResultsThe chemometric analysis with a line regression (R2) = 0.97 revealed 70% significant similarities in the phytonutrients of samples between the two regions and an intriguing 30% variation within the same plant species. In addition, kaempferol, quercetin, luteolin, tangutorid E, and podophyllotoxin, among others were annotated as the major phytonutrients in the samples. The antioxidant assays unveiled concentration-dependent trends with scavenging activity of up to 98% (half-maximal inhibitory concentration [IC50] = 0.14 mg/mL) for 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 87% (IC50 = 0.28 mg/mL) for hydrogen peroxide assay. All the test extracts did not exhibit good to significant antibacterial inhibitory effect (minimum inhibitory concentration [MIC] = 1.25 mg/mL) compared to ciprofloxacin (MIC = 0.0156–0.0039 mg/mL).ConclusionThe variations in the phytonutrients of the same M. oleifera species harvested from different countries could have dire consequences including potential health risks and even death. This study should serve as a benchmark toward the phytonutrients and marketing implications on the quality of products formulated with samples harvested from different growth environments and exists as a reference for further research into the cultivation and marketing of M. oleifera leaves in South Africa.